Desorption and diffusion characteristics of methane in the non-ventilation working face. (15th October 2022) - Gao, Tao; Deng, Cunbao; Han, Qing
Highlights: The positive pressure desorption and diffusion characteristics of CH4 were studied. Desorption volume and rate of CH4 decrease with the increase of positive pressure. Diffusion coefficient of CH4 decreases with the increase of positive pressure. Temperature and pressure are the key factors affecting positive pressure diffusion. Abstract: Based on the rapid development of intelligent unmanned mining technology in coal mines, a new concept of non-ventilation working face is put forward. In the absence of ventilation, it is more possible to extract high purity methane and eliminate coal mine accidents. There are few studies on the desorption and diffusion characteristics of methane under constant positive pressure (higher than atmospheric pressure) in the non-ventilation working face. In this study, a set of self-designed gas positive pressure desorption equipment was used to carry out desorption experiments under various positive environmental pressures. The diffusion coefficient of methane in coal was calculated by using the unipore diffusion model. The results indicate that the extended Langmuir EXT1 model can well describe the variation of methane desorption capacity with time under different positive pressures. Under the same temperature and equilibrium pressure, the limit desorption capacity and desorption rate of methane in coal decrease with the increase of external positive pressure. With the increase of temperature and equilibrium pressure, the negative effect of positive pressure is weakened. At the same temperature and equilibrium pressure, the diffusion coefficient of methane in coal decreases with the increase of positive pressure. The higher equilibrium pressure increases the methane concentration in coal matrix and weakens the influence of positive pressure on the concentration difference, which slows down the decreasing rate of diffusion coefficient. On the contrary, the increase in temperature reduces the methane concentration in coal matrix and accelerates the decreasing rate of diffusion coefficient. These results provide theoretical guidance for the realization of the non-ventilation working face.